Constructivist Learning Theory: The Contribution to Foreign Language Learning and Teaching - Suhendi, A; ., Purwarno (KnE Social Sciences, 2018)
This study deals with John Dewey’s constructivism. Dewey’s theory in Jia (2010) is the main idea or theory of conducting this study. The idea of using constructivism theory is not a new theory in educational teaching and learning in Indonesia. The Dewey’s theory states that constructivism can build individual and social knowledge and it is then the result of this study. The essence contained in constructivism theory is the meaning of a learning process. Dewey in Jia (2010) claims that knowledge is uncertain. Knowledge must be applied because it is an interpretation of reality. Case study is the approach used in this study to ensure the validity of the research result (Kothari. 2004). Thus, the purposes of this study are: (1) to shed the light on the schools of constructivism, and (2) to clarify the principles of constructivism in general and language teaching in particular as its contributions in the classroom activities. The result shows that constructivism contribute positive impact on educational progress as to improve students ability because constructivism opens the learner’s curiosity about something new. Students can also build their knowledge to create, and design something related to their needs. Keywords: constructivism, language learning, language teaching, constructivism principles